Characterization and risk stratification of prostate cancer in patients undergoing radical cystoprostatectomy. (4th February 2013) - Buse, Stephan; Höfner, Thomas; Müller, Stephan C; Hermann, Edwin; Wieland, Wolf F; May, Matthias; Stief, Christian G; Bastian, Patrick J; Hohenfellner, Markus; Haferkamp, Axel
Abstract : Objective: To describe the prevalence of incidental prostate cancer in patients undergoing radical cystoprostatectomy for bladder malignancy; to quantify the association between incidental prostate cancer and mortality in these patients; and to quantify the association between incidental prostate cancer and age in radical cystoprostatectomy specimens. Methods: Consecutive patients undergoing radical cystoprostatectomy for bladder malignancy at six academic institutions were assessed. End‐points were the histological diagnosis of prostate cancer in the radical cystoprostatectomy specimens and mortality. The association between incidental prostate cancer and mortality was calculated by multivariable Cox regression, and the association between age and the occurrence of prostate cancer was calculated by logistic regression. Results: A total of 1122 patients (aged 65.6 ± 10 years) were included in this analysis. Prostate cancer was detected in 17.8% ( n = 200) of the cystoprostatectomy specimens. After multivariable adjustment, prostate cancer was significantly associated with mortality (hazard ratio 1.27, 95% confidence interval 1.03–1.56). There was a significant association between age and the presence of prostate cancer in the cystoprostatectomy specimen. The odds ratio for the presence of prostate cancer was 1.028 (95% confidence interval 1.011–1.045; P < 0.001) per each year after the age of 40 years. Conclusions: Concomitant prostate cancer is an independent prognostic factor for mortality after radical cystoprostatectomy for bladder cancer. When considering a prostate‐sparing technique, urologists should consider that every fifth to sixth patient will present with a concomitant prostate cancer, and that after the age of 40 years, the odds of a concomitant prostate cancer increases by 2.8% per year, thus warranting a careful balance between the oncological risks and quality of life issues.